Real-life MDA solving business problems with model driven architecture - Guttman, Michael; Parodi, John. (Amsterdam ; Boston : Elsevier/Morgan Kaufmann Publishers, 2007)
Model Driven Architecture (MDA) is a new approach to software development that helps companies manage large, complex software projects and save development costs while allowing new technologies that come along to be readily incorporated. Although it is based on many long-standing industry precepts and best practices, such as UML, it is enough of a departure from traditional IT approaches to require some "proof of the pudding." Real-Life MDA is composed of six case studies of real companies using MDA that will furnish that proof. The authors' approach MDA projects by describing all aspects of the project from the viewpoint of the end-users--from the reason for choosing an MDA approach to the results and benefits. The case studies are preceded by an introductory chapter and are followed by a wrap-up chapter summarizing lessons learned. * Written for executives, analysts, architects, and engineers positioned to influence business-oriented software development at the highest levels. * Filled with concrete examples and analyses of how MDA is relevant for organizations of various sizes. * Considers a range of uses for MDAfrom business process analysis to full-scale software modeling and development. * Presents results for each case study in terms of tangible, measured benefits, including automatically generated code, defect reduction, improved visibility, and ROI.
Introduction -- Compuware / State of Ohio Job and Family Services -- Soluta.net / Coopservice case study: facilities management industry -- Select business solutions / Austrian Health Authority -- Inherit / Harris case study: telecommunications industry -- Data access technologies/GSA : executable enterprise architecture -- Interactive objects/Daimler case study : autootive Industry -- Summing up the parts.
Includes bibliographical references and index.
Keywords: Information technology -- Management -- Case studies; Computer software -- Development -- Case studies; Software architecture -- Case studies; System design -- Case studies; Management information systems -- Case studies; Information technology -- Management; Computer software -- Development; Software architecture; System design; Management information systems; Electronic books; Case studies